Analysis of Character Building of “Environmental Consciousness” in Fifth Grade Elementary School Students Through Greening Programs - Sa'adiah; Dewi Masithoh (Journal Of Applied Multidisiplinary Studies, 2025)
Globalization and modernization have changed cultural norms in Indonesian society. Awareness of protecting the environment remains low. Schools can help build environmental conservation awareness. This study analyzes environmental consciousness through a greening program for elementary students. The present study is of the survey type. The research was conducted from January 2023 to March 2024. The research was conducted in SD NU Sleman Yogyakarta. The subjects of this study were fifth-grade students. The research sample was obtained through simple purposive sampling, comprising 69 students, 47 male and 22 female, representing the population of all students at SD NU Sleman Yogyakarta. The data collection technique employed a questionnaire guideline, with the research instrument being a questionnaire sheet (closed questionnaire). The data obtained from the questionnaire was then subjected to analysis using the Person Product Moment formula to ascertain its validity, with its reliability being determined through the implementation of the Cronbach's Alpha formula. The study found that greening programs can promote environmental awareness in students. The environmentally conscious character is made up of three parts: 1) environmental awareness, 2) love for the environment, and 3) sustainability. It received a total score of 7088 (82.18% in the "very strong" category)